Tumor-associated macrophages in human breast cancer produce new monocyte attracting and pro-angiogenic factor YKL-39 indicative for increased metastasis after neoadjuvant chemotherapy - Liu, Tengfei; Riabov, Vladimir; Klüter, Harald; Kzhyshkowska, Julia (OncoImmunology, 2018)
In breast cancer, the tumor microenvironment plays a critical role in the tumor progression and responses to therapy. Tumor-associated macrophages (TAMs) are major innate immune cells in tumor microenvironment that regulate intratumoral immunity and angiogenesis by secretion of cytokines, growth factors as well as chitinase-like proteins (CLPs), that combine properties of cytokines and growth factors. YKL-39 is a chitinase-like protein found in human and absent in rodents, and its expression in TAMs and role in breast cancer progression was not studied to date. Here for the first time we demonstrate that YKL-39 is expressed on TAMs, predominantly positive for stabilin-1, but not by malignant cells or other stromal cells in human breast cancer. TGF-beta in combination with IL-4, but not IL-4 alone was responsible of the stimulation of the production of YKL-39 in human primary macrophages. Mechanistically, stabilin-1 directly interacted with YKL-39 and acted as sorting receptor for targeting YKL-39 into the secretory pathway. Functionally, purified YKL-39 acted as a strong chemotactic factor for primary human monocytes, and induced angiogenesis in vitro. Elevated levels of YKL-39 expression in tumors after neoadjuvant chemotherapy (NAC) were predictive for increased risk of distant metastasis and for poor response to NAC in patients with nonspecific invasive breast carcinoma. Our findings suggest YKL-39 as a novel therapeutic target, and blocking of its activity can be combined with NAC in order to reduce the risk of metastasis in breast cancer patients.